The progress of maritime discovery : from the earliest period to the close of the eighteenth century, forming an extensive system of hydrography - Clarke, James Stanier, 1765?-1834 (Cambridge : Cambridge University Press, 2014)
James Stanier Clarke (c.1766-1834) was a chaplain and naval author. An associate of the Prince of Wales, Clarke was a naval chaplain before being appointed chaplain at Carlton House. He is best remembered for founding the Naval Chronicle with his colleague John McArthur, and published various scholarly works concerning the British Navy. This volume, first published in 1803, contains Clarke's study of early navigational methods and naval history. Originally conceived as the first volume of a multi-volume work encompassing the development of maritime technology until the eighteenth century, this volume focuses on early navigational methods and discoveries in antiquity and the Medieval periods until 1498. Arranged chronologically according to civilisation or country, Clarke describes in detail the navigational methods and naval discoveries of early societies.
Also issued in print: 2010.
Originally published: London: T. Cadell, and W. Davies, 1803.
Description based on online resource; title from PDF title page (viewed on April 26, 2021).
Keywords: Discoveries in geography; Discoveries in geography -- Portuguese; Voyages and travels -- Bibliography; Geography -- Bibliography